PENERAPAN BALANCED SCORECARD SEBAGAI TOLOK UKUR PENGUKURAN KINERJA PADA RUMAH SAKIT UMUM DAERAH DI KABUPATEN KARANGANYAR - Bambang Widarno, Siti Faizatun Imro’ah, Suharno & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2018)
The purpose of this research is to know the performance measurement of Karanganyar Regional General Hospitals by using balanced scorecard method, where performance measurement using four perspectives, the finance perspective, customer perspective,internal business process perspective, and the growth and learning perspective. This reseach using primary and secondary’s data. Primary data from questionnaire which divided to families/patients of Karanganyar’s General regional hospitals for measuring satisfaction of customer. While secondary data using finacial data 2016 - 2017, totally patient data 2016 - 2017, totally employes data 2016 - 2017 which following traine and totally bed’s data 2016 - 2017. Sample 80 patients as respondents who have been selected by using accydental sampling. Method of this research using descriptive. The result of all about performance measurent by balanced scorecard is include category good enough which score 77,5 or (60-80). Finacial perspective is fluctuating and category is good enough, customer perspective’s category is good enough, process business internal perspective’s category is good enough because there are two new product/fasilities (inovation) and operations process are increasing in totally visiting’s patient 2016 - 2017. Growth and learning perspective’s category is good because there are increasing employes who following traines ss2016 - 2017. The result of this reseach can be conclused that performance’s measurent can be used as reference for performance measurent in the next future which is comprehensive. Keywords: performance measure, balanced scorecard, hospital.